Forensic Analysis and Removal of Date-Rape Drug Present in the Spiked Drinks - Murugan Aadolin Prabha; Arputharaj Samson Nesaraj; Manasai Arunkumar (Journal of Forensic Science and Medicine)
Background: Beverages play a positive role in a balanced diet. Beverages can provide an enjoyable and refreshing mind to reach a particular target. In beverages, date-rape drugs, such as Rohypnol, gamma-hydroxybutyric acid, and ketamine, were usually added to make victims to become weak, confused, unconscious, and vulnerable. Aims and Objectives: The aims and objectives of the research work are to analyze the beverages, viz., Sprite, Coca-Cola and Coffee by analytical techniques and to degrade the date-rape drug present in the beverages by photocatalysis using activated carbon as the photocatalyst material. Materials and Methods: The drug (clonazepam) and beverages used in the research work were analyzed using FTIR, UV and HPLC techniques. Results: From the FTIR, in beverages (Sprite and Coca-Cola), the peaks corresponding to C-O and O-H functional groups confirmed the presence of CO2 and H2O and in Coffee, the presence of νas (COC) and νs (COC) vibration bands is found out. The UV-visible analysis confirmed the λmax value for activated carbon as 251 nm. Under visible light and activated carbon photocatalyst, 53.57% of drug molecule was degraded from coca cola which was found to be highest than other beverages. The degradation of drug molecule was also confirmed by the reduction in the peak area for a particular retention time through HPLC analysis. Conclusion: Photocatalysis can be effectively used to remove any drug present in the spike drinks.